Barriers to participation in classical music events by young Czechs - Tamášiová, Laura; Karlíček, Miroslav, 1979-; Vítová Dušková, Marie; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2024)
Barriers to participation in classical music events by young Czechs. The thesis aims to delve into the factors influencing young Czechs (aged 18-24) in their participation in classical music events. It seeks to uncover both the barriers preventing their engagement and the motivating factors driving their attendance. Additionally, the research will explore the attitudes and motivations of these individuals concerning classical music and music in general. Lastly, the study will investigate the musical preferences of young Czechs. This thesis highlights three distinct dimensions of the research: 1. Barriers and Motivating Factors in Classical Music Engagement: This dimension of the research focuses on uncovering the obstacles that deter young Czechs (aged 18-24) from participating in classical music events. It will delve into issues such as ticket costs, accessibility, lack of awareness, or perceptions of exclusivity specific to classical music. Simultaneously, it seeks to identify the motivating factors that drive young individuals to attend classical music events. These motivations could include personal interest, educational experiences, cultural significance, or social influences unique to classical music. 2. Attitudes and Motivations Towards Classical Music and Music in General: This dimension explores the broader attitudes and motivations of young Czechs concerning classical music specifically. It examines their perceptions of classical music's relevance, its role in society, and any preconceived notions about its complexity or accessibility. Additionally, it investigates their general attitudes and motivations towards music as a whole, encompassing various genres and forms of musical expression. This allows for a comparison between classical music and other genres, revealing unique insights into their preferences. 3.
Musical Preferences Among Young Czechs: The third dimension of the research concentrates solely on the musical preferences of young Czechs. It delves into their choices when it comes to music genres, artists, and live music experiences. This dimension takes a comprehensive approach, examining not only classical music but also popular, contemporary, and alternative genres to gain a comprehensive understanding of the musical landscape within this age group. By structuring the research in this manner, the study can thoroughly investigate the complexities of young Czechs' engagement with classical music, distinguish their attitudes and motivations regarding classical music from those related to music in general, and provide a comprehensive overview of their diverse musical preferences across different genres and styles. Goals of the Master’s Thesis: 1. Identifying Barriers: To explore and identify the specific barriers that prevent young Czechs aged 18-24 from participating in classical music events. This includes analyzing differences in barriers faced by active concert attendees and passive fans. 2. Understanding Motivations: To understand the motivations and interests of young Czechs in classical music and music in general and determine how these factors influence their attendance at such classical events or events in general. 3. Analyzing Musical Styles and Preferences: To analyze different musical styles and preferences among young Czechs, encompassing classical music as well as popular, contemporary, and alternative genres. 4. Exploring Attitudes and Perceptions: To explore the attitudes and perceptions of young Czechs towards classical music and classical music events, including any stereotypes or misconceptions they may hold. Methodology: Qualitative Approach The research will employ a qualitative methodology to gain a deep and nuanced understanding of the factors influencing young Czechs' participation in classical music events and music generally. Th
Vedoucí práce: Miroslav Karlíček
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses